THE ROLE OF COMMUNITY POLICING IN CRIME PREVENTION AND MANAGEMENT EFFORT (STUDY AT GORONTALO RESORT POLICE) - Waluyo Amu, Robby; Hanapi, Yayan; Aisa Kodai, D.; Tumuhulawa, Arifin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The National Police of the Republic of Indonesia as one of the institutions that has the task of maintaining stability and realizing internal security includes maintaining security and order and law enforcement in the community. In the effort to prevent and overcome crime, community policing carried out by Bhayangkara Pembina Community Security and Order or abbreviated as Bhabinkamtibmas has a very important role. The legal basis for implementing Community Policing is the National Police Chief Regulation Number 3 of 2015 concerning Community Policing. The main task of bhabinkamtibmas is to develop community policing in the village, so bhabinkamtibmas is placed in the village or sub-district in order to reduce the crime rate in the area or village by realizing its main tasks and functions. However, in practice, the role of community policing has not been maximally implemented. This is because there are factors that hinder it, for example the limited number of personnel that is not proportional to the size of an area, especially in the jurisdiction of the Gorontalo Police and there are still many members of Bhabinkamtibmas who have not received police education in the field of Binmas and Intelkam. The method used in this paper is using empirical research methods, legal research based on the facts obtained in the field. The role of Community Policing carried out by Bhabinkamtibmas in crime prevention and control is very important because with the role they carry out they can help solve problems faced by the community.